Pemberdayaan Masyarakat Pesisir Payum Melalui Eko-Literasi - Ilham, Mohamad; Fredy, Fredy; Ismail, My; Yohanes, Rizki Adri; Rapsanjani, Hafsemi; Day, Wa Ode Siti Hamsinah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The Payum coastal area possesses abundant natural resources; however, challenges such as low basic literacy, limited economic skills, and minimal environmental awareness hinder the community's progress. The Empowerment of the Payum Coastal Area through Eco-Literacy program aims to enhance community capacity through three literacy approaches: basic literacy, economic literacy, and environmental conservation literacy. The methods applied include basic literacy teaching using a fun learning approach for children and teenagers, fishball-making training as a form of economic literacy for housewives and youths, and environmental conservation activities to improve ecological awareness and appreciation of local wisdom. The results of the program showed a significant improvement in basic reading, writing, and arithmetic skills for 87.18% of the basic literacy participants. About 50% of the economic literacy participants successfully produced and marketed fishballs independently. Meanwhile, the environmental conservation activities resulted in the planting of 100 mangrove seedlings and improved understanding of coastal ecosystems among 92.50% of participants. In conclusion, this program effectively provided positive impacts on improving basic literacy, economic skills, and environmental awareness among the Payum coastal community. The program's sustainability requires ongoing support, regular mentoring, and collaboration with various stakeholders to enable the community to become economically self-sufficient, educationally empowered, and environmentally conscious.